2005
DOI: 10.1007/s10886-005-4245-1
|View full text |Cite
|
Sign up to set email alerts
|

Antennal Electrophysiological Responses of Three Parasitic Wasps to Caterpillar-Induced Volatiles from Maize (Zea mays mays), Cotton (Gossypium herbaceum), and Cowpea (Vigna unguiculata)

Abstract: Abstract-Many parasitic wasps are attracted to volatiles that are released by plants when attacked by potential hosts. The attractiveness of these semiochemicals from damaged plants has been demonstrated in many tritrophic systems, but the physiological mechanisms underlying the insect responses are poorly understood. We recorded the antennal perception by three parasitoids (Cotesia marginiventris, Microplitis rufiventris, and Campoletis sonorensis) to volatiles emitted by maize, cowpea, and cotton plants afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 35 publications
6
73
0
4
Order By: Relevance
“…7, which is published as supporting information on the PNAS web site). These insect-inducible plant volatiles have established roles in the positive associative learning and attraction of natural enemies (22,23). Inceptin and OS also increased cinnamic acid levels, a product of L-phenylalanine ammonia-lyase and precursor to phenylpropanoid defenses induced by biotic attack (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…7, which is published as supporting information on the PNAS web site). These insect-inducible plant volatiles have established roles in the positive associative learning and attraction of natural enemies (22,23). Inceptin and OS also increased cinnamic acid levels, a product of L-phenylalanine ammonia-lyase and precursor to phenylpropanoid defenses induced by biotic attack (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Electroantennogram studies have shown that some minor compounds elicit strong antennal responses in these parasitoids (Gouinguené et al, 2005), and current attempts to isolate and identify key attractants for C. marginiventris indicate an important role for minor compounds (M. D'Alessandro and T.C.J. Turlings, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…1. B) Comparison of the polar fraction to the entire silica extract in methanol below the detection level of the GC analyses (Gouinguené et al 2005). These observations strongly suggest that minor, yet unknown compounds, play a crucial role in the attraction of C. marginiventris to Spodoptera-induced maize volatiles.…”
Section: Discussionmentioning
confidence: 99%